Pengaruh Sektor Potensial Terhadap Kesempatan Kerja Di Kabupaten Bangli - Widyastiti Sravishta, Dewa Ayu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 4, April 2014 (pp. 124-172), 2014)
The aim of this study was to determine how the effect of potential sectors on employment in Bangli regency. The development of potential sector is expected to provide the opportunities in employment and reduce unemployment. The data used in this study is a secondary data obtained from Bali Province and Bangli Regency statistic. The analytical tool used in this study is Ordinary Least Square (OLS), which is this analysis can help to estimate how much the potential sectors influence the employment in Bangli regency. The potential sectors in Bangli regency are agricultural sector, mining sector, and manufacturing sector. Based on the research, the mining sector has a great influence on employment in Bangli regency. Development of uncontrolled mining sector will have lots of negative impact on the conservation and the environment, so it needs special attention from the goverment in developing potential sectors to remain sustainable and in harmony with the environment.
Keywords: potential sector; employment